The impact of the direct effects of sulfate and black carbon aerosols on the subseasonal march of the East Asian subtropical summer monsoon. Issue 6 (18th March 2016) - Wang, Dongdong; Zhu, Bin; Jiang, Zhihong; Yang, Xiu‐Qun; Zhu, Tong
Abstract: Aerosol emissions have rapidly increased in East Asia since the late 1970s. During the same period, the East Asian summer monsoon has shown a weakening trend. In this work, the direct effects (DE) of sulfate and black carbon (BC) aerosols on the subseasonal (pentad mean) march of the East Asian subtropical summer monsoon (EASSM) are investigated using an interactive global climate‐chemistry model. The simulation results suggest that the DE of sulfate aerosols have a notable effect on the cooling of the low troposphere across the continent in spring and autumn, hence, changing the time of the seasonal transition of the zonal land‐sea thermal contrast (ZTC). The DE of BC result in cooling of the low troposphere and heating of the middle troposphere, leading to a different impact than that caused by sulfates. The cooling of the surface and troposphere by sulfates leads to a delay in the warming of East Asian continent in spring and the EASSM onset time; it also accelerates the process of the continent turning colder and advances the retreat of the EASSM. The deeper heating in the middle‐upper troposphere than the cooling in the low troposphere due to the DE of BC or the combination of both lead to an advance in the onset time of the monsoon caused by the continent turning warmer earlier in spring. In autumn, the same cooling effect by sulfates leads to the continent turning colder earlier, resulting in an advance in the retreat time. Key Points: Aerosol direct effects could change the zonal land‐sea thermal contrast Sulfate and BC have an opposite effects in the middle parts of the troposphere Aerosol direct effects change the East Asia subtropical summer monsoon march